Spatial spillover effects of environmental regulation on ecological industrialization: Evidence from the upper reaches of the Yangtze River - Wangying Xie; Yun Qing; Lixia Tao; Wenyu Li; Chuanhao Wen (International Review of Economics & Finance, 2025)
In the context of China's ecological civilization initiative, understanding the spatial spillover effects of environmental regulation on ecological industrialization in the upper reaches of the Yangtze River is essential for fostering a synergistic relationship between environmental regulation and industrial development. This synergy promotes the supply of high-quality ecological products and supports the transformation of “lucid waters and lush mountains” into “gold and silver mountains.” Drawing on data from 47 cities in the region between 2005 and 2022, this study employs the global Moran's I index, local Moran's I scatter plots, the spatial Durbin model, and spatial effect decomposition methods to explore these spillover effects. The results show that command-and-control, market-based, and public participation environmental regulations all exhibit significant spatial spillover effects on ecological industrialization. Threshold effect tests further reveal that the impact of environmental regulation on ecological industrialization varies according to per capita GDP levels. Mechanism analysis highlights green technological innovation as a key driver of the positive effects of environmental regulation on ecological industrialization. These findings provide novel theoretical insights into the spatial effects and mechanisms underlying the interaction between environmental regulation and ecological industrialization.